Candidates for inclusion in a universal antiretroviral regimen: are lamivudine and emtricitabine interchangeable?. Issue 4 (July 2017) - Ford, Nathan; Vitoria, Marco; Doherty, Meg; Gray, Andy
Abstract : Purpose of review: Lamivudine (3TC) and emtricitabine (FTC) are the most widely used antiretroviral medications worldwide and are considered by the WHO to be interchangeable. This article reviews evidence supporting interchangeability of 3TC and FTC and considerations for future use. Recent findings: Three randomized trials have directly compared the safety and efficacy of 3TC and FTC against identical backbone regimens. Each of these trials reported a nonsignificant difference in virological suppression, and when results were pooled the overall difference was nonsignificant (relative risk 1.03, 95% confidence interval 0.96–1.10). These findings of equivalence are further supported by indirect evidence from nine randomized trials comparing 3TC and FTC against a similar backbone regimen of two different nucleoside reverse transcriptase inhibitors (relative risk of virological suppression 0.99, 95% confidence interval 0.96–1.01). Data from observational studies is mixed. Overall, reported differences between 3TC and FTC in observational studies are often associated with differences in the baseline characteristics of the treatment groups, notably with respect to immunological and virological status, comorbidity, substance misuse, and pill burden. Summary: The totality of evidence to date, from pharmacological data to observational studies to direct and indirect comparisons in randomized trials, suggests that 3TC and FTC can be considered to be therapeutically interchangeable and that if there are any differences, these are likely to be very small and not of major clinical importance.